Variation characteristic and mechanism of carbon isotope composition of coalbed methane under different conditions and its tracing significance. (15th October 2021) - Tao, Mingxin; Chen, Xiangrui; Li, Zhongping; Ma, Yuzhen; Xie, Guangxin; Wang, Yanlong; Wei, Lingjun; Wang, Zuodong; Tang, Xiuyi
Highlights: The research has the most types of gas samples and the most comprehensive basic data at present. The composition, variation trend and mechanism of CBG δ 13 C1 were revealed. The tracer significance and application scope of CBG δ 13 C1 under different conditions are put forward. It is of great significance to enrich the theory of CBG isotope geochemistry. Abstract: Coalbed gas (CBG) is a form of new energy with a large resource potential. The δ 13 C1 is an important indicator in trace CBG origins and thermal evolution degrees. However, regarding CBG δ 13 C1 as a genetic tracer still exists uncertainty. Here, we systematically studied the distribution characteristics, variation mechanisms and applications of the δ 13 C1 of CBG samples produced under different conditions. The study shows CBG δ 13 C1 are highly variable and complex. The δ 13 C1 are from −79.5‰ to −10.1‰, and the correlation between δ 13 C1 and Ro is week. The δ 13 C1 of the production gas and coal core desorption gas are stable and could be used as an effective genetic tracer. The δ 13 C1 of the mining coal desorption gas are significantly higher than the theoretical δ 13 C1, however, the δ 13 C1 of the drained coalmine gas are lower, suggesting that the mining coal desorption gas represents the residual CBG, however, the drained coalmine gas represents the first desorbed CBG. Therefore, their δ 13 C1 cannot be used as genetic tracer, but have great potential in tracing the CBG prevention condition. The mixture of secondary biogenic gas (SBG) and thermogenic gas makes δ 13 C1 high variability. It cannot be directly used as tracer, but is of great significant in study the mixing ratios of the two kinds of gases. The main reasons for the high variability and complexity of CBG δ 13 C1 are the isotope desorption fractionation and the mixing of SBG and thermogenic gas. This study provides a new scientific basis for geochemical tracing and resource evaluation of CBG.